MERAJUT UKHUWAH DALAM KEGIATAN MUHARRAM DI MASJID AT-THIIN DESA LUBUK SAHUNG KECAMATAN SUKARAJA KABUPATEN SELUMA - Fahimah, Iim; Karlenata, Hiis; Rifqi M., Faishal; Tri Ariska, Vera; Jauhari, Fatima (CV. Kalimasada Group, 2024)
This project is one of the programs of the Real Work Lecture of Islamic University Students. Fatmawati Sukarno State University (UINFAS) Bengkulu Group 97 in Lubuk Sahung Village. The program. This program is designed to commemorate Islamic holidays, besides that this program is also expected to increase the religious value of the community in Lubuk Sahung Village. Religious values to the community in Lubuk Sahung Village, and also strengthen the relationship between the community. Among the community. Methods methods used included an initial survey to identify how the culture and habits of the community in Lubuk Sahung village, the preparation of an activity plan, and the participation of the local community. participation of the local community. The expected result is the creation of close friendship that is able to increase the value of togetherness and also community's awareness of the Islamic New Year's holiday, which coincides on the 1st of Muharram.